ANALISIS SWOT PROGRAM PERUBAHAN DIRI DARI HATI (PERIH) DALAM MENINGKATKAN KARAKTER DAN KEDISIPLINAN SISWA DI SMAN 1 LONG BAGUN - Norkumala Dewi; Intan Beauty Kusnukiandany; Syifa' Hanum Budiawati; Supriadi; Nurlaili; Usfandi Haryaka (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This article presents a comprehensive SWOT analysis of the "Perubahan Diri dari Hati" (PERIH) program implemented at SMAN 1 Long Bagun, Mahakam Ulu Regency, East Kalimantan. The PERIH program is a school innovation that prioritizes an educational consequence approach as a humanistic alternative to conventional punishment in order to shape student character and discipline. This program is rooted in the philosophy of Ki Hadjar Dewantara and is reinforced by the theory of Positive Discipline and Restorative Practices International. Data were collected through a qualitative descriptive approach using direct observation, semi- structured in-depth interviews, and a Likert-scale Google Form questionnaire (1–5). Data were then analyzed using the interactive analysis model of Miles and Huberman (1994). The findings indicate that the program has strong philosophical and institutional strengths, supported by collaboration across school actors. However, weaknesses include the consistency of standard operating procedures (SOPs), limited supporting facilities, and the absence of a formal evaluation system. Opportunities are wide open through the Independent Curriculum policy and the potential for program replication to other border schools. The main threats stem from the flood-prone geographical conditions and sustainability risks due to personnel turnover. A development strategy based on the SWOT matrix (SO, WO, ST, WT) was formulated to ensure continued quality improvement and program sustainability.